Illustrating Student Mathematics Identities Through a Network of Identity Frameworks. Issue 5 (28th May 2023) - Voigt, Matthew; Wynn, Lynda; Bjorkman, Katie; Lo, Stanley M.
Abstract : In this paper, we briefly introduce three theoretical frameworks for mathematical identity and why they matter to practitioners teaching undergraduate mathematics courses. These frameworks are narrative identities, communities of practice, and figured worlds. After briefly describing each theory, we provide examples of how each framework can be used to interpret or inform classroom discourses by applying the framework to a selected transcript from a student-centered mathematics project called the Catwalk problem. We summarize how an awareness of students' forming mathematical identities can be used positively in the undergraduate classroom to help educators support students to form productive mathematical identities.